Magnetic properties of iron-rich Fe-Sc glasses - COEY, JOHN MICHAEL DAVID (American Physical Society, 1989)
Amorphous FexSc100-x alloys with x=89, 90, and 91, prepared by melt spinning, exhibit a single sharp spin-freezing transition at 100 3 K to an asperomagnetic state. The average Fe57 hyperfine field at 4.2 K is 22.7 T. Magnetization curves indicate that fields in excess of 20 T would be required to achieve saturation at 4.2 K and that the iron moment extrapolated to infinite field is 1.6B. Hysteresis is found at low temperatures. On hydrogenation, the alloys become soft collinear ferromagnets with an iron moment of 2.2B and a Curie point of 310 K. A magnetic phase diagram is presented that summarizes the magnetic properties of a-FexM100-x systems (M=Sc,Y,Zr, or Hf). The behavior when M is a IIIb element (Sc,Y) is distinct from that when it is a IVb element (Zr,Hf), suggesting that the direct iron-iron exchange is frustrated by an indirect antiferromagnetic coupling in the IIIb alloys. Both groups tend to a common limit as x 100.. AE
PUBLISHED
Keywords: Physics